2022
DOI: 10.1051/matecconf/202236405002
|View full text |Cite
|
Sign up to set email alerts
|

The investigations on properties of self-healing concrete with crystalline admixture and recycled concrete waste

Abstract: The concept of self-healing concrete is becoming more necessary as sustainability in construction is more desirable. Amongst the current solutions in this technology are autogenous, chemical, and bacterial self-healing. It is paramount that secondary raw materials be used in the production of selfhealing concrete as a form of a sustainable solution. Therefore, in this paper, the admixture “Betocrete-CP-360-WP”, which is a crystallizing waterproofing admixture with hydrophobic effect and is 100% recyclable, has… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 16 publications
(21 reference statements)
0
4
0
Order By: Relevance
“…When it comes to surface damage due to freeze/thaw cycles, the air-entraining agent is evidently the most effective additive for preventing damage, almost equally effective regardless of whether freezing/thawing occurs with or without salt presence, while the negative effect of the crystalline hydrophilic additive is significantly more pronounced during freezing/thawing in the presence of salt. Such research findings on the impact of the crystalline hydrophilic additive are even worse than the results presented in [51]. Specifically, Manhanga et al [51] concluded in part of their study addressing the scaling of concrete exposed to a 3% sodium chloride solution that the crystalline hydrophilic additive (in amount of 0.8% per cement weight) does not affect this type of damage caused by freeze-thaw cycles.…”
Section: Discussionmentioning
confidence: 88%
See 3 more Smart Citations
“…When it comes to surface damage due to freeze/thaw cycles, the air-entraining agent is evidently the most effective additive for preventing damage, almost equally effective regardless of whether freezing/thawing occurs with or without salt presence, while the negative effect of the crystalline hydrophilic additive is significantly more pronounced during freezing/thawing in the presence of salt. Such research findings on the impact of the crystalline hydrophilic additive are even worse than the results presented in [51]. Specifically, Manhanga et al [51] concluded in part of their study addressing the scaling of concrete exposed to a 3% sodium chloride solution that the crystalline hydrophilic additive (in amount of 0.8% per cement weight) does not affect this type of damage caused by freeze-thaw cycles.…”
Section: Discussionmentioning
confidence: 88%
“…Such research findings on the impact of the crystalline hydrophilic additive are even worse than the results presented in [51]. Specifically, Manhanga et al [51] concluded in part of their study addressing the scaling of concrete exposed to a 3% sodium chloride solution that the crystalline hydrophilic additive (in amount of 0.8% per cement weight) does not affect this type of damage caused by freeze-thaw cycles.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…Self-healing concreate is another widely discussed smart building material in the literature. Numerous techniques, including autogenous, chemical, and bacterial self-healing, are used in self-healing concrete to repair the material's structural integrity (Manhanga et al, 2022). Cracks and other damage on the building can be self-healed, thus enhancing the building's lifespan and reducing the need for expensive repairs (Chen et al, 2023).…”
Section: Literature Reviewmentioning
confidence: 99%